Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Loyalitas Pelanggan Pada Ayu Salon Limboto - Pindi Puluhulawa; Deby Rita Karundeng; Elfis Mus Abdul (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the influence of service quality and facilities on custumer loyalty at Ayu Salon Limboto. Primary data were collected through questionnaires using an accidental sampling multiple linear regressiom with the assistance of SPSS software. The result reveal that (1) service quality has a negative but not significant effect on customer loyalt, (2) facilities have a positive and significant effect on customer loyalty, and (3) service quality and facilities simultaneously have a positive and significant affect on customer loyalty. These findings indicate that improvements in facilities contribute more significantly to customer loyalty than enhancements in service quality. This study provides practical efforts to insrease customer loyalty.